Effects of previous steroid treatment on ischemic stroke outcomes: a propensity score-matched hospital analysis - Yasser Alatawi; Eman A. Alraddadi; Eman A. Alraddadi; Abdullah A. Alhifany; Faisal E. Alzahrani; Faisal E. Alzahrani; Saud M. Alknawy; Saud M. Alknawy; Nawaf M. Aljohani; Nawaf M. Aljohani; Husun K. Kecheck; Husun K. Kecheck; et al. (Frontiers in Pharmacology)
IntroductionStroke is a leading cause of morbidity and mortality worldwide, and its recurrence poses significant challenges to patient management and healthcare systems. This hospital-based retrospective observational study investigated the association between prior exposure to systemic corticosteroids and stroke recurrence within the Saudi Arabian population.MethodsA multicenter retrospective study included acute-subacute adult ischemic stroke patients. Propensity score matching (PSM) was applied to balance baseline characteristics between the steroid and non-steroid groups. The primary outcome was the incidence of stroke recurrence within 365 days of the index stroke. Secondary outcomes included stroke severity and functional independence on admission and discharge, hemorrhagic transformation within 30 days, and mortality rate within 365 days of the index stroke.ResultsOut of 925 patients, 85 (9.19%) received steroids. After PSM, the analysis included 254 patients, with 33.46% in the steroid group and 66.54% in the control group. Steroid-exposed patients had significantly lower National Institutes of Health Stroke Scale (NIHSS) scores at both admission (median 5 [interquartile range (IQR): 1–8] vs 6 [IQR: 3–10], p = 0.0087) and discharge (median 1 [IQR: 0–4.5] vs 4 [IQR: 2–9], p = 0.0001), but higher modified Rankin Scale (mRS) scores at discharge (median 5 [IQR: 4–5] vs 4 [IQR: 3–5], p = 0.0004). Univariate analysis revealed significant associations between steroid exposure and a reduced likelihood of aphasia (OR: 0.33, 95% CI: 0.17–0.67, p = 0.0020) and dysarthria (OR: 0.51, 95% CI: 0.30–0.88, p = 0.0149). Conversely, steroid exposure was linked to increased risks of pneumonia (OR: 2.08, 95% CI: 1.22–3.55, p = 0.0071), deep vein thrombosis-pulmonary embolism (DVT-PE) (OR: 2.70, 95% CI: 1.30–5.62, p = 0.0079), and impaired consciousness (OR: 1.80, 95% CI: 1.06–3.04, p = 0.0303). In the multivariate analysis, steroid exposure was associated with an increased risk of stroke recurrence (OR: 1.98, 95% CI: 1.01–3.87, p = 0.0471). However, this association did not retain significance after adjusting for confounders (OR: 1.14, 95% CI: 0.44–2.96, p = 0.7874).ConclusionThe study revealed that steroids were associated with significantly lower stroke severity but higher mRS scores. However, the risk of stroke recurrence was similar between the two groups. Moreover, the use of steroids may increase the risk of complications in stroke patients, such as pneumonia and DVT-PE. Future studies with larger sample sizes and more detailed data on steroid use and stroke outcomes are required. These studies would provide more definitive insights and guide clinical decision-making regarding the use of steroids in stroke management.